Uma investigação sobre paradigmas tecnológicos e abordagens pedagógicas dos tutores inteligentes nos sistemas de ensino-aprendizagem - Monaco, Fabíola Maria (Universidade Federal de São Carlos, 2008)
This research work has as its starting point the conjecture posed by Oliveira regarding a possible technicist reflux yielded by the dissemination of new information and communication technologies (ICTs) over varying extents (political, economical, scientific etc.), highlighting its incidence on the implementation of its resources in the domain of the methods and techniques of education. In this context, focusing on the Intelligent Tutoring Systems (ITS) as a representative instance of such educational technologies (with novel paradigms with respect to other media such as data extraction and computation and information inference), this investigation aims at assessing and explaining, through the pedagogical perspective, the possible occurrence of approximations to the technicism. The methodology relies on the in-depth study of the ITS based on the pedagogical paradigms which ground the focused educational technology, being the method of analysis that of established models and processes of the System Engineering field, in which ITS are effectively developed as artifacts. The results identify and explain non-intentional technicists approximations that are not inherent neither to the conception nor to the implementation, but to an intermediary phase of the process corresponding to the system design. In addition, some considerations are drawn on the difficulties and hindrances found in the disciplinary study of interfacing technologies
Keywords: Ensino aprendizagem; Tecnologia educacional; Ensino programado. 4. Sistemas tutoriais inteligentes; Engenharia de sistemas; Abordagem pedagógica; Paradigma tecnológico; CIENCIAS HUMANAS::EDUCACAO